2020
DOI: 10.3349/ymj.2020.61.10.875
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adverse Drug Reactions with Carbamazepine and Oxcarbazepine at a Tertiary Care Hospital

Abstract: Purpose: To describe adverse drug reactions (ADRs) to carbamazepine (CBZ) and oxcarbazepine (OXC), including severe cutaneous ADRs, at a tertiary care hospital over a 10-year period. Materials and Methods: The frequency and clinical features of ADRs caused by CBZ and OXC were analyzed using the pharmacovigilance database and spontaneous ADR reporting data of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The main limitations of carbamazepine are potential drug interactions and the risk of severe adverse reactions, such as Stevens–Johnson syndrome. Oxcarbazepine has a similar structure and efficacy but a better safety profile (though it can cause severe skin reactions) ( 29 ). Its use slightly increased during the 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of carbamazepine are potential drug interactions and the risk of severe adverse reactions, such as Stevens–Johnson syndrome. Oxcarbazepine has a similar structure and efficacy but a better safety profile (though it can cause severe skin reactions) ( 29 ). Its use slightly increased during the 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Among the psychotropic drugs carbamazepine was causally linked to DRESS syndrome the most frequently in the past: recent systematic review of published case reports and other types of observational studies involving patients with DRESS syndrome found that carbamazepine, lamotrigine, phenytoin, valproate, and phenobarbital were the most implicated drugs [8]. Carbamazepine, lamotrigine, phenytoin and phenobarbital share a commonality in their molecular structure that could be important for pathophysiological mechanism of the events underlying the DRESS syndrome -aromaticity [9]. Why aromatic antiepileptic drugs are more prone to cause DRESS syndrome is not known but one of the published case series showed that patients who experienced DRESS syndrome after taking one of the aromatic antiepileptic drugs tolerated non-aromatic anticonvulsants well later on [10].…”
Section: Discussionmentioning
confidence: 99%
“…9 /l)/(%)1.48/ 52.13 4.44 / 78,38 5.0 / 73.93 4.9/ 41.2 4.4/ 27.14 3.51 / 39.73 Lymphocytes (10 9 /l)/(%) 1.09/ 38.42 0.…”
mentioning
confidence: 99%
“…The Food and Drug Administration of the United States recommended the labeling of the drug as to be screened for this genetic marker before its use [ 10 ]. Oxcarbazepine is a newer antiepileptic drug that has shown fewer adverse drug reactions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%